Obtention and Products Distribution of Bioliquid from Catalytic Pyrolysis of Tomato Plant Waste - Buitrago Buitrago, José Luis (2025)
The use of tomato plant residues (i.e., stems, leaves, etc.) as a substrate for catalytic pyrolysis of biomass was investigated. A comprehensive study was conducted to investigate the impact of catalysts on the performance of different pyrolysis fractions (i.e., gas, biosolid, waxes, and bioliquid) as well as the distribution of products within the bioliquid. The catalysts employed in this study were derived from two distinct types of zirconia. The first type was synthesized by a conventional sol-gel method, while the second type was prepared with a modified method aimed at improving the presence of mesopores. This modification involved the incorporation of Pluronic 123. These materials were designated ZrO2 and ZrO2P25, respectively. Both types of zirconia were used as supports for tungstophosphoric acid (H3PW12O40, TPA), a heteropolyacid with a Keggin structure, in the preparation of catalysts with strong acid sites. The results demonstrated that the bioliquid yield of the non-catalytic fast pyrolysis of tomato plant waste was approximately 23% and that the obtained bioliquid contained a wide variety of molecules, which were detected and quantified by GC-MS. In the presence of the catalysts, both the bioliquid yield and the distribution of bioliquid products were substantially modified. Furthermore, the possible sugar degradation pathways leading to the formation of the molecules present in the pyrolytic bioliquids were thoroughly examined. The results obtained from this study indicate that the physicochemical characteristics of the catalysts, specifically their pore size and acidity, have a significant impact on the selectivity of the catalytic processes towards valuable molecules, including anhydro-sugars and furanic derivatives such as furfural and furfuryl alcohol.